The Effect of Lime Addition on the Compressive Strength Improvement of Paving Blocks Write - Harahap, Muhammad Rizki (SENTRI: Jurnal Riset Ilmiah, 2025)
Paving blocks are made by mixing the composition of cement, sand, water and or with other additives, then pressure is applied with a certain intensity. The use of paving blocks is becoming more widespread, causing alternative additives to be sought that can increase compressive strength. Lime is selected as an additional alternative material in the paving block mixture. Lime is relatively easy and cheap because this material is a potential in Indonesia which spreads to various islands, namely in Java, Sumatra and Irian Jaya, so the availability of this material is very much. This study aims to determine the effect of adding lime on the compressive strength of paving blocks. The composition of the mixture in this study is the quality of class D. The compressive strength of this class D is compared to the compressive strength of the paving block with the addition of lime. The percentage of lime addition is 2%, 4%, 6%, 8%, and 10% to the weight of cement. The cement used is PCC (Portland Cement Comcomposite) type and the test specimen is printed in a hexagonal shape using manual tools. The results of laboratory tests obtained that the sand sludge content and grain fineness modulus (MHB) were qualified. The maximum increase in compressive strength occurs with the addition of 8% lime. According to SNI-03-0691-1996, the compressive strength of 8% lime is classified as class C quality. Meanwhile, the addition of 10% lime at the age of 28 days resulted in a decrease of 17% in the compressive strength of the addition of 8% lime.